Effects of arbuscular mycorrhizal fungi on flavonoid content in Astragali Radix cultivated in cadmium-contaminated soils - Meng, Xiu-xin; Jia, Xia; Zhao, Yong-hua (Frontiers in Microbiology, 2025)
IntroductionAs bioactive components in Astragali Radix (AR), flavonoids can promote hematopoiesis and have hypolipidemic properties, among others, and they are easily affected by environmental factors. Arbuscular mycorrhizal fungi (AMF) can influence flavonoid synthesis in plants exposed to heavy metals by expanding the root absorption area to establish a reciprocal symbiotic relationship with most plants.MethodsWe investigated the effects of Funneliformis mosseae and time on the total flavonoids and key monomers (calycosin, calycosin-7-glucoside, formononetin, and ononin) in AR exposed to cadmium (Cd) using a pot experiment. The treatments consisted of non-inoculation and F. mosseae inoculation. A two-way analysis of variance and Duncan’s test were conducted.ResultsShoot total flavonoids decreased (p < 0.05) at 60 (20.5%) and 90 d (18.3%), while formononetin decreased (83.4%) by 120 d; conversely, calycosin-7-glucoside increased (p < 0.05) with inoculation, although calycosin-7-glucoside decreased (p < 0.05) over time from 60 to 120 d regardless of inoculation. Shoot calycosin increased (p < 0.05) over time regardless of inoculation. Root total flavonoids decreased (p < 0.05) by 15.2% at 60 d, then increased (p < 0.05) by 23.5% at 90 d, along with increases in formononetin (117.1%) and ononin (59.6%) at 60 d, and calycosin-7-glucoside (21.2%) at 120 d, which increased (p < 0.05) under inoculation. The colonization rate, along with shoot Cd, C, P, H, and C/N ratio, significantly affected shoot flavonoids, while Cd accounted for 90.0% of flavonoid variation, which may be associated with its impact on flavonoid synthase. The variation in root flavonoids was significantly influenced by root S, biomass, and N, suggesting that AMF regulation may vary between AR organs. Calycosin-7-glucoside was significantly affected by phenylalanine ammonia-lyase (a key gene in flavonoid synthesis). Overall, F. mosseae led to significant increases in shoot total flavonoids and calycosin-7-glucoside. The total flavonoids were higher in shoots than in roots, indicating that annual AR shoots exposed to Cd may be utilized for medicinal purposes under inoculation.DiscussionThese results provide insights into the enhancement of AMF on the quality of medicinal plants grown in Cd-contaminated soils, and the long-term effects of AMF on flavonoids at varying Cd levels should be further investigated.